Nilai Moral dalam Novel Surat Kecil untuk Tuhan Karya Agnes Davonar - Usi Karundeng; Desi Sukenti (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The first moral action is based on the human heart itself. If the heart is dissatisfied with what it has, it will do what is right or what is wrong. This study uses a qualitative descriptive method, which is a research procedure with the results of presenting descriptive data in the form of the author's speech in the novel Small Letters for God. Based on the results of the discussion in this study, it can be concluded that the aspect of responsibility towards himself can be seen from the main character, namely Keke who is responsible for carrying out his duties both regarding education and regarding responsibility for his recovery. The aspect listed in moral values ​​is conscience. One of the characteristics of moral values ​​is that only these values ​​give rise to a "voice" from the conscience that accuses us of belittling or opposing moral values ​​and praises us for embodying moral values. In the novel Little Letters to God by Agnes Davonar, there are many moral values, namely the character Keke who feels homesick for her mother figure, and Keke who has a strong curiosity about her illness. In the novel Little Letters to God by Agnes Davonar, there is a moral value of obligation to the characters Keke and Pak Jody's shop. The moral value related to obligations is that obligations towards ourselves should not be understood as obligations solely towards ourselves, but also an obligation to carry out worship. In the small surak for god novel there are two characters that contain a moral value of obligation, namely the characters Keke and Pak Jody.